Draught beer hygiene: cleaning of dispense tap nozzles - Quain, David E. (Wiley, 2016)
Draught beer quality can be compromised by the growth of spoilage microorganisms. Whilst best practice for assuring dispense hygiene is broadly recognized, it is not always fully or regularly implemented. In some markets, tap nozzles are removed and stored overnight at room temperature in carbonated (soda) water. The next morning they are returned (sometimes after rinsing) to the dispense tap. The effectiveness of this approach is compared with soaking in diluted line-cleaning solution (UK best practice)or a solution containing hypochlorous acid (commercial sanitizing tablets). Two novel approaches – ozonated water and use of ultrasonics – were also evaluated. Bioluminescence analysis of microbial attachment to the inner surfaces of nozzles showed that soaking in carbonated water resulted in gross contamination. Sanitizing tablets achieved ‘commercial sterility’ and a 4-log reduction in bioluminescence compared with carbonated water. The efficacy of hypochlorous acid was confirmed by incubating cleaned nozzles in fresh beer without any increase in turbidity. Diluted line-cleaning solution was less effective and achieved a 2-log reduction. Ultrasonics reduced microbial attachment but effectiveness was aligned to increasing process time. Soaking in ozonated water was without antimicrobial impact. This work has shown carbonated water to be ineffective in cleaning microbiologically contaminated nozzles. This is a concern as these microorganisms derive from the dispense line, the environment and likely human interaction. To minimize the risks of transfer to dispensed product or back-contaminating the dispense line, soaking draught beer nozzles in an effective sanitizing solution is strongly recommended.